High Risk of Early Cataracts in Young Type 1 Diabetes Group: A Nationwide Cohort Study. (9th October 2020) - Lu, Wen-Li; Shen, Po-Chih; Lee, Chen-Hao; Su, Yu-Tsun; Chen, Li-Min
Abstract : Background . Chronic hyperglycemia in type 1 diabetes (T1D) patients results in ocular problems over time, but only a few studies emphasized on cataracts. Aim . To evaluate the epidemiology of cataracts in the T1D population. Method . A two-part study was conducted using data from the National Health Insurance Research Database in Taiwan. Information from the Longitudinal Health Insurance Database (LHID) was served as a template of the general population. In the first part, a total of 3, 622 T1D cases registered between 1998 and 2007 were enrolled and compared with a matched group from the LHID. For identifying risk factors of cataracts in the T1D population in the second part, a total of 9032 T1D cases registered between 1998 and 2013 were included. Result . Compared to the LHID, the hazard ratio (HR) of cataracts in the T1D group was 5.81 (95% CI 4.60–7.33), and the HR was higher in females (6.29, 95% CI 4.63–8.55). The peak incidence of cataracts occurred between age 20 and 29 in the T1D group, while in the LHID, it was after 60. The overall incidence of cataracts in the T1D group was 9.1%. In T1D patients with cataracts, they were found with higher rates of associated diabetic complications. Conclusion . Compared to the nondiabetic population, cataracts seemed more rampant and premature in T1D patients, especially those of female gender. Early ophthalmologic examination should be considered in T1D patients.